Studying a collection of common-wheat varieties for leaf rust resistance, crop yield and grain quality in the environmental conditions of Novosibirsk region - L. P. Sochalova; V. A. Aparina; N. I. Boyko; E. V. Zuev; E. V. Morozova; E. V. Musinov; N. A. Vinichenko; I. N. Leonova; V. V. Piskarev (Вавиловский журнал генетики и селекции)
The relationship between a variety’s genotype, environmental conditions and phytopathogenic load are the key factors contributing to high yields that should be taken into account in selecting donors for resistance and high manifestation of valuable traits. The study of leaf rust resistance in 49 common wheat varieties was carried out in the field against the natural pathogen background and under laboratory conditions using single-pustule isolates with virulence to Lr9 and Lr24. It has been shown that the varieties carrying alien genes Lr6Agi2 (Tulaikovskaya 10) and Lr6Agi1 (Voevoda) were resistant to leaf rust infection both in the field and in the laboratory. Varieties KWS Buran, KWS Akvilon, KW 240-3-13, and Etyud producing crop yields from 417 to 514 g/m2 comparable to the best standard variety Sibirskaya 17 can be reasonably used as Lr24 resistance gene donors under West Siberian conditions. Oms kaya 44 variety showing crop yield of 440g/m2 can be used as a donor for Lr19 and partially effective Lr26. Varieties Tuleevskaya and Altayskaya 110 with Lr9 in their genomes are recommended for the development of resistance gene-pyramided genotypes. The highest protein and gluten contents were observed in the CS2A/2M sample, while KWS Buran, Altayskaya 110, Volgouralskaya, and KWS Akvilon showed the lowest values. Varieties CS2A/2M, Tulaikovskaya 10, Pavon, and Tuleevskaya were ranked the highest in micro- (Cu, Mn, Zn, Fe) and macronutrient (Ca, Mg, K) contents among the common wheat samples from the collection, while the lowest values for most elements were observed in KWS Buran, Novosibirskaya 15, and Volgouralskaya. Winter varieties demonstrating leaf rust resistance against the infectious background typically carry adult plant resistance genes (Lr34, Lr12, and Lr13), particularly combined with the juvenile Lr26 gene. The presence of Lr41 in a winter type line (KS 93 U 62) allowed it to maintain resistance against a leaf rust pathogen clone kLr24, despite the presence of Lr24 in the genotype. Varieties Doka and Cheshskaya 17 may act as donors of resistance genes Lr26 + Lr34 and Lr9 + Lr12 + Lr13 + Lr34, as well as sources of dwarfing without losses in winter hardiness and yield under West Siberian conditions.